Feasibility assessment of the alumina‐forming duplex stainless steels as accident tolerant fuel cladding materials for light water reactors. (18th December 2019) - Kim, Chaewon; Kim, Hyunmyung; Jang, Changheui; Kim, Kangsan; Kim, Yonghee; Lee, Seungjae; Jang, Hun
Summary: Previously, the Fe‐based alumina‐forming duplex stainless steels (ADSSs) were developed for the application of accident tolerant fuel (ATF) cladding materials for light water reactors (LWRs). The on‐going research activities focusing on the feasibility assessment of ADSS alloys for ATF cladding are summarized. A long‐term corrosion behavior in simulated LWR environment and short‐term corrosion resistance in steam environment at temperature range of 800°C to 1200°C were performed, and the results showed excellent corrosion resistance of ADSS alloys. The tensile properties of ADSS alloys were evaluated at room temperature to 550°C, which showed much higher strength compared with other Fe‐based alloys. After accelerated thermal aging at 425°C for 1000 hours, strength of ADSS alloys was increased and the elongation was decreased. However, the elongation of aged ADSS alloys was still greater than 15% because of the presence of ductile austenite phase. Meanwhile, because of the neutron absorption by Ni, Cr, and Fe, the use of ADSS alloys as ATF cladding would have detrimental effects on the fuel cycle length. Nonetheless, it was assessed that the neutronics penalty could be readily overcome by adopting thinner fuel cladding and slightly higher fuel enrichment. Finally, the fabrication of thin‐walled tube was introduced. Overall, it has been shown that ADSS alloys could be considered as candidate alloys as ATF cladding materials. Abstract : Fe‐based alumina‐forming duplex stainless steels (ADSS) showed excellent corrosion resistance in simulated LWR environment and steam environment at temperature range of 800 – 1200 °C. Despite the thermal aging, the elongation of aged ADSS alloys was still greater than 15% because of the presence of ductile austenite phase. The neutronics penalty could be readily overcome by adopting thinner fuel cladding and slightly higher fuel enrichment.